1-3 John - Bennett, Thomas Andrew. 1981- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2021)
"An exegetical commentary on 1-3 John with special attention to theological concerns"--
Introduction: The two horizons of the Letters of John -- Interpretation : theological interpretation of 1-3 John -- Theological horizons of 1-3 John.
Includes bibliographical references (pages 211-216) and indexes.
Keywords: Bible. -- Commentaries; Commentaries